Sintesa dan Karakterisasi Biokomposit Poly(L-Lactid Acid)/Cellulose Acetate dan Aplikasinya sebagai Adsorben Bead - Nugrahaning Dwi Prastiwi; Eko Vindy Utami; Hikmatun Ni’mah; Eva Oktavia Ningrum (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
Biocomposite materials comprised of poly(L-lactic acid) (PLLA) and cellulose acetate (CA) were preparedthrough solvent blending technique. The obtained biocomposite films were characterized by using dynamicmechanical analysis (DMA) and thermogravimetric analysis (TGA). The biocomposites were then applied asadsorbent bead for dye separation. The properties and adsorption performance of the biocomposite beadswere also observed in term of morphology, surface area and adsorption capacity. The composition ofPLLA/CA in weight ratio was varied: 100/0; 75/25; 50/50; 25/75; 0/100. The dye used in this research foradsorption analysis was methylene blue (MB). The MB adsorption was done in two pH conditions which areneutral and base (pH=10) conditions. The mechanical properties of biocomposites PLLA/CA films showedthe slightly decrease in tensile strength after the addition of CA until 50 wt% and then increased again forhigher CA content. However, the young modulus continuously increased with CA content. The elongation atbreak of biocomposite PLLA/CA films showed higher value of elongation at break compared to the pristinePLLA and CA. On the other hand, the thermal stability of biocomposites increased with the increasing of CAcontent compared to that of pristine PLLA. The increase in thermal stability was caused by the specificproperty of CA which is high thermal resistant. For its application, the beads could only be obtained fromthe biocomposite with higher CA composition, PLLA/CA (25/75) and (0/100). The morphology of PLLA/CAbeads showed spherical shape with porous structure on their surface. Adsorption performance measurementshowed that the adsorption capacity and % removal of the PLLA/CA (25/75) bead increase compared to thepure CA bead.